UPAYA PENCEGAHAN DEMENSIA DENGAN PELATIHAN TERAPI OTAK DAN PEMERIKSAAN KESEHATAN DASAR PADA LANJUT USIA DI WILAYAH KELURAHAN BULAKREJO KABUPATEN SUKOHARJO - Tutik Yuliyanti; Kustanti Kustanti; W Wahyuni (P3M Universitas Aisyiyah Surakarta, 2022)
Abstract The aging process causes deterioration of the brainâ€™s ability and memory, one of the prevention is cognitive therapy. The target of this activity is for the elderly in the Bulakrejo area to understand information about brain therapy and practicing brain therapy as well as knowing their health status through basic health checks. Methods of implementation: identification of the elderly, health checks, health education, brain therapy, nursing care. The result of intelligent brain therapy activities showed that the elderly were able to answer 85% of the questions correctly. Brain therapy with puzzle games 54% of the elderly are able to remember the shape of the object they are seeing, 46% of the elderly are able to improve their thinking skills and 100% of the elderly can increase their social interaction.In the chain message game 54% of the elderly are able to remember the massages received and describe the meaning given. Health examination results: 48,5% elderly in the pre hypertensia category, 46,6% experiencing hyperuresemia, 20% experiencing hyperglycemia, 15,4% experiencing hyperlipidemia. Conclusion: brain stimulation therapy can train memory and basic health checks can detect health status as an effort to prevent dementia in the elderly. Â Keywords: dementia; brain therapy; elderly